2014
DOI: 10.1002/jbmr.2347
|View full text |Cite
|
Sign up to set email alerts
|

Higher Glucocorticoid Secretion in the Physiological Range Is Associated With Lower Bone Strength at the Proximal Radius in Healthy Children: Importance of Protein Intake Adjustment

Abstract: Whether higher production of glucocorticoids (GCs) within the physiological range may already be affecting bone status in healthy children is unknown. Because dietary protein intake affects both bone and GCs, we examined the association of urinary measures of glucocorticoid status and cortical bone in healthy non-obese children, after particularly controlling for protein intake. Proximal forearm bone parameters were measured by peripheral quantitative computed tomography (pQCT). Subjects studied (n = 175, 87 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 61 publications
1
16
0
1
Order By: Relevance
“…Reduced bone formation at trabecular bone sites and increased endocortical resorption are the most consistent pathological findings of glucocorticoid excess (12). In healthy children, higher adrenal glucocorticoid secretion within the normal hormonal range has been associated with smaller cortical area resulting from larger endosteal and lower periosteal circumference (13). Half of our patients had current daily hydrocortisone equivalent dose above 20 mg/day (0.32 mg/kg), although the presently recommended hydrocortisone dose is between 0.2-0.3 mg/kg (14).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced bone formation at trabecular bone sites and increased endocortical resorption are the most consistent pathological findings of glucocorticoid excess (12). In healthy children, higher adrenal glucocorticoid secretion within the normal hormonal range has been associated with smaller cortical area resulting from larger endosteal and lower periosteal circumference (13). Half of our patients had current daily hydrocortisone equivalent dose above 20 mg/day (0.32 mg/kg), although the presently recommended hydrocortisone dose is between 0.2-0.3 mg/kg (14).…”
Section: Discussionmentioning
confidence: 99%
“…Only recently we could show in healthy children that moderately elevated cortisol and cortisone metabolitesstill fully within the normal physiological range-are independently associated with lower BMD and bone strength parameters at the proximal radius [19]. The proof of such subtle long-term effects does usually require a number of sophisticated methodological efforts regarding sample collection (e.g., 24-h urines), dietary recording (e.g., 3-day weighed dietary records), and specific biomarker and hormone metabolite measurements (e.g., gas chromatographymass spectrometry steroid profiling) which can explain that not every study will uncover corresponding physiological relationships between bone status and moderate elevations of glucocorticoids or other biomarkers.…”
mentioning
confidence: 89%
“…The mere quantification of cortisol (in blood, urine, or saliva) may not always suffice to appropriately identify functional hypercortisolism. For this, the additional measurement of cortisone can be particularly useful, since cortisone is efficiently activated to cortisol in many tissues and it increasingly emerges as an important player in glucocorticoid-mediated endocrine effects [17][18][19].…”
mentioning
confidence: 99%
“…3 A previous report from the Dortmund Nutritional and Anthropometric Longitudinally Designed Study showed significant correlation between higher glucocorticoid hormone levels and impaired bone characteristics in children. 6 Thus, one possible extrapolation is that higher dietary acid loads lead to impaired bone formation in children. However, higher dietary protein intake, a major component of PRAL, actually correlates with greater bone mineral content and bone strength.…”
mentioning
confidence: 99%
“…7 It was only after controlling for protein intake, that is, for the major component of PRAL, that higher glucocorticoid hormone levels correlated with impaired bone characteristics in children. 6 Thus, increased dietary protein intake appears to correlate with improved bone characteristics, but “excessive” glucocorticoid hormone response may blunt these benefits. Also, increases in NAE are important in the response to higher PRAL.…”
mentioning
confidence: 99%